2011
DOI: 10.1093/cvr/cvr288
|View full text |Cite
|
Sign up to set email alerts
|

PI3Kγ inhibition reduces blood pressure by a vasorelaxant Akt/L-type calcium channel mechanism

Abstract: Overall our findings suggest that PI3Kγ inhibition could be a novel tool to modulate calcium influx in vascular smooth muscle cells, thus relaxing resistance arteries and lowering blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…PI3K/Akt signaling promoted voltage-dependent trafficking of Ca 2ϩ channels to the plasma membrane that increased Ca 2ϩ influx via L-type VOCC and thereby was involved in the myogenic response in mouse second-order mesenteric arteries (197,910). Genetic knockdown of Dicer for 5-6 wk to reduce the global role of microRNAs (miRNAs) lowered BP and myogenic tone in mesenteric arteries by reducing PI3K/Akt signaling and L-type VOCC activity (specifically the ␣2␦1 subunit) (101).…”
Section: Renal Autoregulatory Mechanismsmentioning
confidence: 99%
“…PI3K/Akt signaling promoted voltage-dependent trafficking of Ca 2ϩ channels to the plasma membrane that increased Ca 2ϩ influx via L-type VOCC and thereby was involved in the myogenic response in mouse second-order mesenteric arteries (197,910). Genetic knockdown of Dicer for 5-6 wk to reduce the global role of microRNAs (miRNAs) lowered BP and myogenic tone in mesenteric arteries by reducing PI3K/Akt signaling and L-type VOCC activity (specifically the ␣2␦1 subunit) (101).…”
Section: Renal Autoregulatory Mechanismsmentioning
confidence: 99%
“…In the last decade, a consistent piece of literature demonstrated the expression of PI3Kγ in cardiovascular system cells [5,15,16], as vascular smooth muscle cells (VSMCs) [36]. In this regard, it has been shown that PI3Kγ is involved in hypertension [16,17] by regulating vascular function [17] and particularly myogenic tone, defined as the physiological behavior of resistance arteries to counteract perfusion pressure increases and mainly relying on the constrictor tone of VSMCs [17,36,37,38].…”
Section: Pi3kγ: a Focus On Their Signaling Pathway In Cardiovasculmentioning
confidence: 99%
“…In this regard, it has been shown that PI3Kγ is involved in hypertension [16,17] by regulating vascular function [17] and particularly myogenic tone, defined as the physiological behavior of resistance arteries to counteract perfusion pressure increases and mainly relying on the constrictor tone of VSMCs [17,36,37,38]. Both in experimental animal models of hypertension and in hypertensive patients, it was reported that the increase in peripheral vascular resistances unquestionably contributes to the maintenance of chronic hypertensive status [37,38,39,40,41].…”
Section: Pi3kγ: a Focus On Their Signaling Pathway In Cardiovasculmentioning
confidence: 99%
See 2 more Smart Citations